The Effect of Colloids versus Crystalloids for Goal-Directed Fluid Therapy on Prognosis in Patients Undergoing Noncardiac Surgery: A Meta-Analysis of Randomized Controlled Trials - Wang Niu; Junyi Li; Shouping Wang (Anesthesiology Research and Practice)
Background. Goal-directed fluid therapy (GDFT) contributes to improvements in intraoperative fluid infusion based on objective parameters and has been widely recommended in clinical practice. In addition, increasing evidence reveals that GDFT can improve the prognosis of surgical patients. However, considering the individual characteristics of colloids and crystalloids in clinical use, it is uncertain as to which type of fluids administered is associated with better outcomes in the condition of GDFT. Objectives. To evaluate the effect of colloids versus crystalloids under GDFT on prognosis in patients undergoing noncardiac surgery. Data Sources. Randomized controlled trials (RCTs) from PubMed, EMBASE, Ovid MEDLINE, CNKI, Cochrane library, and reference lists of relevant articles. Methods. Two investigators independently screened and reviewed studies for inclusion and performed data extraction. Our primary outcome was a composite of postoperative complications. The secondary outcomes were (1) mortality at the follow-up duration; (2) postoperative complications of several organ systems, including cardiac, pulmonary, digestive, urinary, nervous system, and postoperative infection events; and (3) hospital and ICU length of stay. Heterogeneity was assessed by the I2 and chi-square tests. The odds ratio (OR) of the dichotomous data, mean difference (MD) of continuous data, and 95% confidence intervals (CI) were calculated to assess the pooled data. Results. Of 332 articles retrieved, 15 RCTs (involving 2,956 patients undergoing noncardiac surgery) were included in the final analysis. When the data were pooled, patients in the colloids and crystalloids group revealed no difference in postoperative composite complications (OR = 0.84, 95% CI = 0.51–1.38, P=0.49) under GDFT. Regarding the secondary outcomes, patients in the colloids group were associated with fewer digestive system complications (OR = 0.64, 95% CI = 0.41–0.98, P=0.04). However, no difference was found in mortality (OR = 1.37, 95% CI = 0.72–2.58, P=0.34), complications of the cardiac system (OR = 1.49, 95% CI = 0.66-3.37, P=0.34), pulmonary system (OR = 0.89, 95% CI = 0.62–1.28, P=0.53), urinary system (OR = 1.05, 95% CI = 0.61-1.80, P=0.87), nervous system (OR = 1.04, 95% CI = 0.55–1.98, P=0.90), postoperative infection events (OR = 0.89, 95% CI = 0.75–1.07, P=0.22), length of hospital stay (difference in mean = −0.71, 95% CI = −1.49–0.07, P=0.07), and ICU stay (difference in mean = −0.01, 95% CI = −0.20–0.18, P=0.95) between patients receiving GDFT with colloids or crystalloids. Conclusion. There is no evidence of a benefit in using colloids over crystalloids under GDFT in patients undergoing noncardiac surgery, despite its use resulting in lower digestive system complications.